Craft fun with Sondra - Clark, Sondra (Minnetonka, Minn. : Meadowbrook, 1999)
A collection of more than fifty craft simple projects, including ribbon boxes, pasta necklases, wind chimes, shakers and tambourines, puppets, cards, and more.
Keywords: Handicraft -- Juvenile literature; Handicraft; Children$1 (Bs writings.s